Ball milling modified SAPO-11 based catalysts for n-Decane hydroisomerization - Ferreira, Luisa (2019)
Bifunctional Pt/SAPO-11 catalysts were prepared using as acid matrix the microporous silico-aluminophosphate, SAPO-11, synthesized under microwave radiation. After synthesis, the material was physically modified using a ball mill, changing the grinding time but keeping frequency constant. The metal function (0.5 wt.% Pt) was introduced through mechanical mixture with commercial Pt loaded alumina. The catalysts were characterized by several techniques: powder X-Ray Diffraction, pyridine adsorption followed by infrared spectroscopy, low temperature N-2 adsorption, Hg intrusion porosimetry and electronic microscopy (SEM). The characterization data show modifications of structural and textural properties of the samples as the milling time increases. The catalytic behaviour of Pt/SAPO-11 materials was studied for hydroisomerization of long chain n-alkanes, using n-decane as model molecule, aiming to increase the production of mono-branched isomers. The catalytic results show that, under optimized milling conditions (60 min; 50 Hz) the selectivity into mono-branched isomers increased when compared with parent catalyst.